Analysis of Competencies, Performance, and Organizational Culture: A Comprehensive Literature Review in the Government Sector - Kabul Swastadi, Petrus; Syamsunasir (Dinasti Publisher, 2025)
This study explores the dynamics of interaction between competence, performance, and organizational culture in the government sector through a qualitative library research approach. The purpose of the study is to analyze the complex mechanisms that affect the effectiveness of government organizations in the context of digital transformation. The research method uses systematic analysis of academic literature from international databases with the PRISMA protocol, including identification, extraction, categorization, and narrative synthesis. The results of the study revealed that competence, organizational culture, and performance have a dynamic interconnection that is influenced by technological, psychological, and structural factors. Digital transformation requires government apparatus to develop adaptive competencies, build a responsive organizational culture, and configure sustainable performance. The research emphasizes the importance of a holistic approach to institutional capacity building, which goes beyond traditional approaches to innovative, inclusive, and meaningful management models.